Kidney Histopathology Can Predict Kidney Function in ANCA-Associated Vasculitides with Acute Kidney Injury Treated with Plasma Exchanges. Issue 3 (March 2022) - Nezam, Dorian; Porcher, Raphaël; Grolleau, François; Morel, Pauline; Titeca-Beauport, Dimitri; Faguer, Stanislas; Karras, Alexandre; Solignac, Justine; Jourde-Chiche, Noémie; Maurier, François; Sakhi, Hamza; El Karoui, Khalil; et al.
Significance Statement: Findings of the international prospective multicenter PEXIVAS trial challenge the role of PLEX in AAV. We conducted a retrospective study of 425 patients: 188 with AAV and renal failure treated with PLEX and 237 not treated. A score to identify patients who would benefit from PLEX was developed. With kidney biopsy data, scores more than seven achieved sensitivity and specificity of 83.1% and 96.0%, respectively, for recommending PLEX. The average effect of PLEX for those with recommended treatment corresponded to an absolute risk reduction for death or KRT at M12 of 24.6%. Patients in the PLEX-recommended group had microscopic polyangiitis, MPO-ANCA, higher serum creatinine, crescentic and sclerotic classes, and higher Brix score. These findings, which require independent validation, could provide guidance in selecting patients with AAV who will benefit from PLEX. Abstract : Background: Data from the PEXIVAS trial challenged the role of plasma exchange (PLEX) in ANCA-associated vasculitides (AAV). We aimed to describe kidney biopsy from patients with AAV treated with PLEX, evaluate whether histopathologic findings could predict kidney function, and identify which patients would most benefit from PLEX. Methods: We performed a multicenter, retrospective study on 188 patients with AAV and AKI treated with PLEX and 237 not treated with PLEX. The primary outcome was mortality or KRT at 12 months (M12). Results: No significant benefit of PLEX for the primary outcome was found. To identify patients benefitting from PLEX, we developed a model predicting the average treatment effect of PLEX for an individual depending on covariables. Using the prediction model, 223 patients had a better predicted outcome with PLEX than without PLEX, and 177 of them had >5% increased predicted probability with PLEX compared with without PLEX of being alive and free from KRT at M12, which defined the PLEX-recommended group. Risk difference for death or KRT at M12 was significantly lower with PLEX in the PLEX-recommended group (−15.9%; 95% CI, −29.4 to −2.5) compared with the PLEX not recommended group (−4.8%; 95% CI, 14.9 to 5.3). Microscopic polyangiitis, MPO-ANCA, higher serum creatinine, crescentic and sclerotic classes, and higher Brix score were more frequent in the PLEX-recommended group. An easy to use score identified patients who would benefit from PLEX. The average treatment effect of PLEX for those with recommended treatment corresponded to an absolute risk reduction for death or KRT at M12 of 24.6%. Conclusions: PLEX was not associated with a better primary outcome in the whole study population, but we identified a subset of patients who could benefit from PLEX. However, these findings must be validated before utilized in clinical decision making.